Simulation of a flexible assembly line - Koh, Chye Teck. (2009)
This dissertation describes the development of a proposal to set up an assembly plant for the manufacture of a group of large-sized medical products. The objective of this work is to enhance competitiveness by reducing the cost of producing these products.